Sosialiasai Nugget Sayur Ikan Patin Untuk Meningkatkan Konsumsi Ikan di Desa Koto Damai Kampar Kiri Tengah - Fazil Hazman; Adhisty Muthia Rani; Dhea Riski Ismaya; Sri Maharani; Muhammad Adrian Maulana; Alfahrur Rahman; Ranee Sly Panggabean; Na’imatul Rodiah; Fakhri Syatu Kunsino; Kartika Kartika (LP2M Universitas Muhammadiyah Enrekang, 2022)
One of the needs of urban communities today is the availability of practical food ingredients, namely those that are ready to cook (ready to be cooked) and ready to eat (ready to eat). Ready of cook means that it takes less time to prepare food. One form of food that is ready to cook is nuggets. Nuggets are one of the foods that are most often consumed and made by everyone, either for their own use, for sale, or for others. Nuggets seem more elegant because this food does not characterize luxury or lack. This socialization aims to increase fish consumption in Koto Damai Village. This socialization uses Factorial Design and Nugget content, which consists of 2 factors. The first factor is the ingredients used to make nuggets, including: Fish Fillet, Catfish, Carrots, Scallions, Garlic, Salt and seasonings, Wheat Flour, Panir Flour, Eggs, and Water. The second factor is the type of fish, namely: Catfish.